2004
DOI: 10.1109/tpami.2004.17
|View full text |Cite
|
Sign up to set email alerts
|

An efficient solution to the five-point relative pose problem

Abstract: An efficient algorithmic solution to the classical five-point relative pose problem is presented. The problem is to find the possible solutions for relative camera pose between two calibrated views given five corresponding points. The algorithm consists of computing the coefficients of a tenth degree polynomial in closed form and, subsequently, finding its roots. It is the first algorithm well-suited for numerical implementation that also corresponds to the inherent complexity of the problem. We investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
447
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,659 publications
(504 citation statements)
references
References 30 publications
2
447
0
2
Order By: Relevance
“…In order to estimate the camera displacement ∆Cam N in each frame, we adopted a simple VO with rotation estimation by Nister's 5-point algorithm [17] and translation by the FSM using features in a ground region close to the camera (details in the Appendix section), similarly to [12]. The parameters (FOV u , FOV v , W, V, H, etc) necessary for the experiments were adopted according to the provided by the KITTI.…”
Section: Applied Vomentioning
confidence: 99%
“…In order to estimate the camera displacement ∆Cam N in each frame, we adopted a simple VO with rotation estimation by Nister's 5-point algorithm [17] and translation by the FSM using features in a ground region close to the camera (details in the Appendix section), similarly to [12]. The parameters (FOV u , FOV v , W, V, H, etc) necessary for the experiments were adopted according to the provided by the KITTI.…”
Section: Applied Vomentioning
confidence: 99%
“…The former case uses image matches made over small displacements to provide an independent estimate of local robot motion, while the latter case treats images as containing information that will allow the robot to recognize its position at a later point in time. A pair of cameras calibrated together can yield metric 6-DOF relative pose estimates, called stereo visual odometry, a technique widely used in terrestrial robotics [Howard, 2008] [Olson et al, 2003, and underwater in [Beall et al, 2010], for example. Underwater, we have found that a DVL generally provides more reliable odometry information over short distances than does a pair of cameras, without any calibration requirements [Kunz and Singh, 2010].…”
Section: Visual Landmarks In the Graphmentioning
confidence: 99%
“…The K matrix allows us to use normalized image coordinates, and gives rise to the essential matrix, which specializes the epipolar geometry to the normalized case. The essential matrix can be estimated from five matched pixels, and it can be decomposed into a 3-D rotation and a translation vector [Nistér, 2004]. This means that even without incorporating any prior estimate of the camera motion from AUV odometry, a pair of image matches in principle can inform five of the six degrees of freedom of the camera motion between two points in time -only the scale of the motion is not recoverable.…”
Section: Constraints Induced By Matched Image Pairsmentioning
confidence: 99%
“…In this calibrated setting, visual odometry is achieved by estimating the essential matrix that relates the homogeneous image coordinates of the same world point in the two viewpoints up to a scale factor [4]. A computationally efficient solution for this was published in the 1990s by Philip [5] and improved upon by Nistér [6]. In Nistérs solution, a RANSAC algorithm evaluates sets of five correspondence points to find the best estimate for the essential matrix.…”
Section: Introductionmentioning
confidence: 99%